Pengaruh Kualitas Pelayanan Terhadap Kepuasan Peserta BPJS Kesehatan Labuhanbatu - Fatimah Zahara Hasibuan; Saparuddin Siregar; S Sugianto (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
Satisfaction is the level of circumstances in which someone states the results of a comparison of the performance of the product or service received and expected. Patient satisfaction will be fulfilled if the process of delivering health services to consumers is in accordance with what they expect or perceived. The purpose of this study is to see whether there is a partial and simultaneous influence between tangible variables, reliability, responsiveness, assurance and empathy for participants' satisfaction of the Health Social Security Organizer. This research is quantitative research and the method used to determine the sample is using the Slovin formula with a sample size of 100 respondents. Data is obtained by distributing questionnaires that have been structured to the respondents. The data analysis technique used is multiple linear regression analysis. The results showed that partially there was a positive and significant effect between direct evidence variables, reliability and assurance with participant satisfaction. Partially responsiveness and empathy did not affect participant satisfaction. Simultaneously the direct evidence variables, reliability, responsiveness, assurance and empathy have a positive and significant effect on the satisfaction of Labuhanbatu Health Social Security Organizer